Pengembangan LKPD Berbasis Proyek IPAS untuk Meningkatkan Berpikir Kritis Siswa Kelas IV - Nisa, Khairatun; Syahfitri, Diani; Ridha, Zaifatur (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to develop a simple project-based Student Worksheet (LKPD) on thr topic of Plant Body Parts ti improve the critical thinking skills of fourth-grade students at MIS Al-Amanah. The research was motivated by the low critical thinking skills of students due to the convevtional IPAS learning approach, which has not provided opportunites for direct experiental learning. The research employed a Research and Development (R&D) method using the 4D model. The subject consisted of three validators: material, language, and design experts, and 10 fourth  grade students who participated in a limited trial. The instruments included validation sheets, students response questionnaires, and critical thingking skill tests. The result showed that the developed LKPD achieved high validity, with 62,5% (valid) from material experts, 91,6% (very valid) from language eperts, and 100% (very valid) from design experts. Thr practicality aspect obtained a student response score od 84,7% (very practical). The effectiveness of the LKPD was reflected in the improvement of pretest and posstest scores with N-Gain of 0,67 (moderate category). Thus, the simple project-based LKPD id fesible, practical, and effective for enchancing students’ critical thinking skills in IPAS learning.